2022
DOI: 10.1016/j.jds.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Optimal concentration of potassium iodide to reduce the black staining of silver diamine fluoride

Abstract: Background/purpose Potassium iodide (KI) is used for reducing the degree of black staining occurred after silver diamine fluoride (SDF) application. However, the optimal KI concentration remains unknown. This study aimed to identify the optimal concentration of KI that effectively reduces black staining after SDF application. Materials and methods Twenty-four extracted teeth with similar pattern of carious lesions were assigned into 6 groups as follows: 1) SDF only, 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 12 publications
0
28
0
6
Order By: Relevance
“… 26 A laboratory study showed that potassium iodide application could reduce the intensity of staining in a dose-dependent manner. 27 However, no significant difference was found 14 days after SDF application. A 30-month clinical trial found that potassium iodide application did not reduce the staining of SDF-treated lesions in the long term.…”
Section: Discussionmentioning
confidence: 89%
“… 26 A laboratory study showed that potassium iodide application could reduce the intensity of staining in a dose-dependent manner. 27 However, no significant difference was found 14 days after SDF application. A 30-month clinical trial found that potassium iodide application did not reduce the staining of SDF-treated lesions in the long term.…”
Section: Discussionmentioning
confidence: 89%
“…When immediately after SDF, KI reacts with the free silver ions in SDF and prevents the formation of silver phosphate [19]. Detsombonnrat et al [20] observed a significant immediate reduction in staining due to SDF following application of KI in a dose dependent manner [20].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Many studies have reported different solutions to overcome this disadvantage and decreasing the staining of the treated teeth such as the application of potassium iodide following the application of SDF [ 23 , 24 , 25 , 26 ]. In terms of parental acceptance, several studies have reported that SDF black staining of teeth was accepted by parents in posterior compared to anterior teeth in addition to other reasons as the child’s cooperation, socioeconomic status, and the need of using sedation or referral to general anesthesia to receive dental treatment [ 12 , 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%